Overall stability analysis of compression struts strengthened with bolted built-up outer casings. (January 2023) - Shi, Hai-Rong; Chen, Ying; Wang, Chun-Lin; Zeng, Bin
Abstract: Strengthening with bolted built-up casing enhances the post-buckling behavior of the compression strut significantly, and the two constitute the assembled-sleeved member. The bolted built-up casing is comprised of two identical components assembled with several slip-critical connections, the flexural mechanism of which is different from the seamless casings. The axial compression tests demonstrated that the slippage of the connections decreased the flexural rigidity and resistance of the assembled casing. Hence, the assembled-sleeved member was more prone to overall stability compared with the seamless. The theoretical analysis was then conducted to assess the flexural resistance of the assembled casing, showing that the flexural failure of the assembled casing initiated with either the steel yielding or the connection slip. The formula of the overall buckling load was further proposed for assembled-sleeved members, which agreed well with the tested results. As for the members with uniformly arranged slip-critical connections, suggestions were provided about the distance between the connections and their shear-bearing capacity so that the assembled-sleeved member can be considered seamless in the overall stability design. Graphical abstract: Unlabelled Image Highlights: The overall stability of assembled-sleeved members is theoretically analyzed. The overall instability is triggered by the steel yielding or the connections slipping. The overall buckling load of assembled-sleeved members is correctly predicted. A design proposal for the arrangement of connections is proposed to avoid slippage.